McArdle Disease vs. Stiff-Person Syndrome: A Case Report Highlighting the Similarities Between Two Rare and Distinct Disorders - Godbe, Kerilyn; Malaty, Giovanni; Wenzel, Alyssa; Nazeer, Sahana; Grider, Douglas J.; Kinsey, Adrienne (Frontiers in Neurology, 2020)
McArdle disease is a rare autosomal recessive disorder of muscle glycogen metabolism that presents with pain and fatigue during exercise. Stiff-Person Syndrome is an autoimmune-related neurologic process characterized by fluctuating muscle rigidity and spasm. Reported is a 41-year-old male who presented to the emergency department due to sudden-onset weakness and chest pain while moving his refrigerator at home. Cardiac workup was non-contributory, but a creatine kinase level > 6,000 warranted a muscle biopsy. The biopsy pathology report was misinterpreted to be diagnostic for McArdle disease given the clinical presentation. After 4 years of treatment without symptomatic improvement, a gradual transition of symptoms from pain alone to pain with stiffness was noted. A positive glutamic acid decarboxylase antibody test resulted in a change of diagnosis to Stiff-Person Syndrome. This is the first known case that highlights the similarities between these two rare and distinct disease processes, highlighting the necessity for thorough history taking, maintenance of a broad differential diagnosis, and knowledge of how best to interpret complex pathology reports.